Essential oils: an alternative for reducing post-harvest losses of fresh bell pepper (Bioagro, 2026)
Bell pepper is an important and nutritious vegetable worldwide. However, due to its high-water content and thin skin layer, its shelf life is short. This study was conducted to evaluate the effectiveness of three essential oils (rosemary, thyme, and lemongrass) as a postharvest treatment on the shelf-life of bell pepper fruits stored for 35 days at 8±1 °C. The findings demonstrated that thyme oil and rosemary oil treatments were the most effective in decreasing weight loss, decay, total yeast and mold counts, and preserving antioxidant capacity. Additionally, thyme oil treatment exhibited the highest antiradical scavenging activity and total phenolic compounds compared to other treatments. Lemongrass oil was the most effective treatment in preserving vitamin C and reducing the respiration rate. Thyme and rosemary treatments were superior in preserving antioxidant capacity in bell pepper fruits. In conclusion, rosemary, thyme, and lemongrass oils could be alternative applications to minimize microbial growth in bell pepper fruits during cold storage.
Keywords: Capsicum annuum; essential oils; postharvest; quality; shelf-life; storage ability